2018
DOI: 10.1002/lary.27497
|View full text |Cite
|
Sign up to set email alerts
|

Sex bias: Is it pervasive in otolaryngology clinical research?

Abstract: Objectives/Hypothesis Recent initiatives highlight substantial sex bias in biomedical research. The objective was to determine whether sex bias is present in otolaryngology and whether sex is appropriately analyzed as an independent variable in otolaryngology clinical research. Study Design Literature review. Methods We systematically reviewed all 2016 articles in three major otolaryngology journals: The Laryngoscope, JAMA Otolaryngology–Head and Neck Surgery, and Otolaryngology–Head and Neck Surgery. Extracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…As a result, the CFD findings can not be generalized to others due to inter-individual anatomic differences (13) . However, this highlights the previously demonstrated importance of providing subject sex and race data so that the applicability (external validity) of the findings can be assessed by the reader (28)(29)(30) . The findings presented here do agree with those of prior studies in different individuals (16)(17)(18)(19)(20) .…”
Section: O R R E C T E D P R O O Fmentioning
confidence: 88%
“…As a result, the CFD findings can not be generalized to others due to inter-individual anatomic differences (13) . However, this highlights the previously demonstrated importance of providing subject sex and race data so that the applicability (external validity) of the findings can be assessed by the reader (28)(29)(30) . The findings presented here do agree with those of prior studies in different individuals (16)(17)(18)(19)(20) .…”
Section: O R R E C T E D P R O O Fmentioning
confidence: 88%
“…13 Our study assesses 2 databases that accurately capture the entire US landscape of clinical trials and burden of disease, avoiding the sampling biases found in previous studies by comparing US data from the ClinicalTrials.gov registry with global disease burden. Although previous investigations narrowed their focus to specific diseases, 7,31,32,34,35 the present study provides novel data, assessing and comparing 17 disease categories. This study's distinct multivariable analysis examines potential factors, including disease category, that may be associated with sex bias among all US-based clinical trials.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Recent studies analyzing high‐impact general surgery and orthopedic surgery literature demonstrated that approximately one‐third of recently published studies performed analysis of outcomes by sex . A similar review of the otolaryngology literature by our institution found similar lack of sex‐ or gender‐based reporting of outcomes in three major otolaryngology journals . Males and females experience many conditions differently, including disease prevalence, symptom manifestations, and response to therapeutics.…”
Section: Discussionmentioning
confidence: 52%